(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
This paper presents the findings of a survey to about theknowledge and use of digital resources by faculty members through CD-ROMdatabases, online databases, online journals OPAC etc available in theengineering college libraries. The subjects chosen for this study were facultymembers affiliated to Devi Ahilya University, Madhya Pradesh, India. Forevaluating study questions and data collection, the questionnaire wasdistributed to a random sample of 160 faculty members. The result of thissurvey are presented and discussed in this paper.